Characteristics of enrolment in an intensive home-visiting programme among eligible first-time adolescent mothers in England: a linked administrative data cohort study. Issue 12 (5th October 2022) - Cavallaro, Francesca L; Gilbert, Ruth; Wijlaars, Linda PMM; Kennedy, Eilis; Howarth, Emma; Kendall, Sally; van der Meulen, Jan; Calin, Maria Andreea; Reed, Lynne; Harron, Katie
Abstract : Background: Intensive home visiting for adolescent mothers may help reduce health disparities. Given limited resources, such interventions need to be effectively targeted. We evaluated which mothers were enrolled in the Family Nurse Partnership (FNP), an intensive home-visiting service for first-time young mothers commissioned in >130 local authorities in England since 2007. Methods: We created a population-based cohort of first-time mothers aged 13–19 years giving birth in English National Health Service hospitals between 1 April 2010 and 31 March 2017, using administrative hospital data linked with FNP programme, educational and social care data. Mothers living in a local authority with an active FNP site were eligible. We described variation in enrolment rates across sites, and identified maternal and FNP site characteristics associated with enrolment. Results: Of 110 520 eligible mothers, 25 680 (23.2% (95% CI: 23.0% to 23.5%)) were enrolled. Enrolment rates varied substantially across 122 sites (range: 11%–68%), and areas with greater numbers of first-time adolescent mothers achieved lower enrolment rates. Mothers aged 13–15 years were most likely to be enrolled (52%). However, only 26% of adolescent mothers with markers of vulnerability (including living in the most deprived areas and ever having been looked after as a child) were enrolled. Conclusion: A substantial proportion of first-time adolescent mothers with vulnerability markers were not enrolled in FNP. Variation in enrolment across sites indicates insufficient commissioning of places that is not proportional to level of need, with mothers in areas with large numbers of other adolescent mothers least likely to receive support.